Performance and digestibility in feedlot lambs fed hay based diets - Oliveira, Euclides Reuter de; Monção, Flávio Pinto; Gabriel, Andréa Maria de Araújo; Fernandes, Alexandre Rodrigo Mendes; Moura, Lais Valenzuela; Nascimento, Felipe de Almeida (Acta Scientiarum. Animal Sciences, 2016)
This study aimed to evaluate the performance of feedlot lambs fed diets formulated with hay of different genotypes of Cynodon spp. and to compare the dry matter digestibility of diets using different evaluation methods (total fecal collection and chromium oxide). Suffolk crossbred neutered male lambs (n=30), with an average age of 90 days and average body weight of 21.5 kg ± 1.6. Diets were formulated using a standard concentrate and hay of the following genotypes of Cynodon dactylon: Jiggs, Vaquero, Tifton 68, Coast-Cross, Tifton 85 and Russell, in a 60:40 forage concentrate ratio, composing the treatments distributed in a randomized block design in a factorial 5 x 2 arrangement of 5 diets and 2 digestibility evaluation methods. Animals receiving Vaquero hay showed dry matter intake of 18.3; 16.9; 25.6; 20.7 and 24.2% higher than those fed hay of Jiggs, Tifton 68, Coast Cross, Tifton 85 and Russell, respectively. There was no difference between diets for digestibility using total fecal collection, chromium oxide and final weight of animals. Jiggs hay based diets allowed greater daily weight gain and better feed conversion.